Irradiation enhances the malignancy-promoting behaviors of cancer-associated fibroblasts - Zhang, Ziyue; Dong, Yi; Wu, Bin; Li, Yingge; Liu, Zehui; Liu, Zheming; Gao, Yanjun; Gao, Likun; Song, Qibin; Zheng, Zhongliang; Yao, Yi (Frontiers in Oncology, 2022)
Background: Cancer-associated fibroblasts (CAFs) are the important component of the tumor microenvironment (TME). Previous studies have found that some pro-malignant CAFs participate in the resistance to radiotherapy as well as the initiation and progression of tumor recurrence. However, the exact mechanism of how radiation affects CAFs remains unclear. This study aimed to explore the effect and possible mechanism of radiation-activated CAFs, and its influence on lung cancer. Methods: CAFs were isolated from surgical specimens in situ and irradiated with 8Gy x-rays. The changes in cell morphology and subcellular structure were observed. CAFs marker proteins such as FAP and α-SMA were detected by Western Blotting. Cell counting kit-8 (CCK8) assay, flow cytometry, wound healing assay, and transwell chamber assay were used to detect the activation of cell viability and migration ability. A nude mouse xenograft model was established to observe the tumorigenicity of irradiated CAFs in vivo. The genomic changes of CAFs after radiation activation were analyzed by transcriptome sequencing technology, and the possible mechanisms were analyzed. Results: The CAFs showed a disorderly growth pattern after X-ray irradiation. Subcellular observations suggested that metabolism-related organelles exhibited more activity. The expression level of CAFs-related signature molecules was also increased. The CAFs irradiated by 8Gy had good proliferative activity. In the (indirect) co-culture system, CAFs showed radiation protection and migration induction to lung cancer cell lines, and this influence was more obvious in radiation-activated CAFs. The radiation protection was decreased after exosome inhibitors were applied. In vivo study also showed that radiation-activated CAFs have stronger tumorigenesis. Transcriptome analysis showed that genes were enriched in several pro-cancer signaling pathways in radiation-activated CAFs. Conclusions: Our study confirmed that CAFs could be activated by ionizing radiation. Irradiation-activated CAFs could promote cancer cell proliferation, migration, radiotherapy tolerance, and tumorigenesis. These results suggested that irradiation-activated CAFs might participate in the recurrence of lung cancer after radiotherapy, and the inhibition of CAFs activation may be an important way to improve clinical radiotherapy efficacy.